Secondary Syphilis Presenting With an Interstitial Granuloma Annulare-Like Histopathologic Pattern: A Report of 2 Cases - João, David Afonso; Pancsa, Tamás; Kicko, Peter; Langerová, Eliška; Šíma, Radek; Hercogová, Jana; Skálová, Alena; Michal, Michal; Kacerovská, Denisa (The American Journal of dermatopathology, 2025)
Syphilis, known as "the great mimicker," is caused by the spirochete Treponema pallidum and is characterized by a diverse array of clinical and histopathologic presentations. In secondary cutaneous syphilis, the most consistent morphological features include a superficial and deep perivascular infiltrate containing plasma cells, varying degrees of endothelial swelling, irregular acanthosis, elongation of rete ridges, a vacuolated pattern, and the presence of plasma cells. Although serologic tests are essential for definitive diagnosis, spirochetes can sometimes be directly identified in silver-stained tissue slides or through immunohistochemistry. Granuloma annulare is a relatively common, benign, self-limiting condition with 3 main variants: conventional, subcutaneous, and interstitial, each with distinct characteristics. In this study, we report 2 cases of cutaneous secondary syphilis with a striking granulomatous reaction pattern that closely mimics the interstitial variant of granuloma annulare. Owing to the severity of the tertiary stage of syphilis, distinguishing between these 2 entities is crucial.
Keywords: Syphilis; Female; Adult; dospělí; Syphilis, Cutaneous; anulární granulom; Humans; diferenciální diagnóza; syfilis; mužské pohlaví; ženské pohlaví; lidé; Male; lidé středního věku; Diagnosis, Differential; Middle Aged; syfilis kožní; Granuloma Annulare